2023
DOI: 10.1051/epjn/2023021
|View full text |Cite
|
Sign up to set email alerts
|

Multi-group analysis of Minor Actinides transmutation in a Fusion Hybrid Reactor

Stefano Murgo,
Marco Ciotti,
Guglielmo Lomonaco
et al.

Abstract: New nuclear technologies are currently being study to face High Level Waste treatment and disposal issues. Generally, GEN-IV fission Fast Reactors (FR) are considered the waste-burners of the future. In fact, a fast flux turns out to be the best choice for actinides irradiation in critical reactors because of favorable cross section conditions. Differently, Fusion Fission Hybrid Reactors (FFHR) are futuristic devices based on the combination of fusion and fission systems and could represent an alternative to F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Future analysis will also regard the actinide target irradiation in the thermal box. In fact, recent studies [26] showed that low-fluence thermal neutron irradiation on HLW may lead to interesting results for waste recycling in FFHR systems. On the other hand, LOMBT is only slightly affected by irradiation.…”
Section: Actinides Conversion Resultsmentioning
confidence: 99%
“…Future analysis will also regard the actinide target irradiation in the thermal box. In fact, recent studies [26] showed that low-fluence thermal neutron irradiation on HLW may lead to interesting results for waste recycling in FFHR systems. On the other hand, LOMBT is only slightly affected by irradiation.…”
Section: Actinides Conversion Resultsmentioning
confidence: 99%